The Financial Dimension of Developing Social Entrepreneurship: Polish and Ukrainian Experiences - Revko, Alona; Verbytska, Anna; Zaharina, Tetyana; Marks‑Krzyszkowska, Małgorzata (Comparative Economic Research. Central and Eastern Europe, 2023)
This paper summarises the arguments within the scientific discussion on the financial dimension of social entrepreneurship. The purpose of the research is to investigate the Polish and Ukrainian experiences of financial foundations for developing social entrepreneurship and, based on the Polish experience, to provide recommendations for social entrepreneurship development in Ukraine. Are view of literary sources and approaches to solving the problem of limited financial resources for social enterprises indicates that state support in Ukraine is in its infancy. The governmental policy should identify the needs of social enterprises and what social problems they will solve. The relevance of these issues is that the level of financial commitment to the development of social entrepreneurship is dependent on the cooperation of various stakeholders, i.e., state authorities and local governmental bodies (regulatory mechanism of financial support), business (mentoring and grant support), higher educational institutions (social entrepreneurship training), and civil society organisations (public awareness, social promotion). The research analyses the experience of financing mechanisms of social entrepreneurship in Poland for recommendations on the development of the domestic financial model for social enterprise support. Based on the Polish experience, government expenditure in the social sphere should go towards organising social entrepreneurship support programs for those social enterprises that use effective models to commercialise the social impact, which will force the development of social businesses. Methodologically, this study is based on a comparative method of analysing the main sources of social enterprise financing in Poland and Ukraine, including public institutions (grants, loans, guarantees, subsidies and prizes) and other international funds. To investigate the financial foundations of social entrepreneurship development, the research determines the variety of revenue sources of social enterprises in Poland and the financial dimension of social enterprises by analysing the level of public and private funding. As the concept of social entrepreneurship is becoming more widespread in Ukraine, the research has significant strategic and applied importance. The research shows that social entrepreneurship in Poland is recognized at the state level as an important tool for achieving social goals in society. The results of the study are particularly relevant in the context of modern challenges, as Ukrainian business owners can take advantage of the analysed European sources of support to start or expand their businesses. As many domestic social enterprises begin to grow, they may think of internationalising their social businesses. The results of the study contribute to the growth of support for the concept of internationalising social business, which has not yet become a common practice in Ukraine. Therefore, in the context of Ukraine today, international expansion maybe a logical step for existing and newly created social enterprises. The tools, resources and mechanisms for supporting social entrepreneurship in Poland identified as a result of the research may help Ukrainian social enterprises overcome obstacles to internationalisation.